2022
DOI: 10.1002/ejoc.202200541
|View full text |Cite
|
Sign up to set email alerts
|

Dual Metallaphotoredox‐Catalyzed Directed C(sp2)−H Functionalization: Access to C−C/C‐Heteroatom Bonds

Abstract: Metallaphotoredox catalysis represents the combination of two activation modes: metal-catalyzed CÀ H functionalization and visible-light-induced photocatalysis. This appealing dual catalysis technique has evolved as a versatile platform that has paved the way for diverse low-energy pathways for a plethora of synthetic transformations. The synergistic combination of two "green" approaches has garnered enormous interest owing to the development of sustainable strategies. In the recent past, significant advanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Over the past decade, metallaphotoredox catalysis has gained significant popularity in synthetic methodology. [21][22][23][24][25][26][27] This approach combines photocatalysis and transition metal catalysis to achieve the modular formation of C-carbon and C-hetero bonds. Specifically, the combination of photocatalytic HAT and transition metal catalysis has enabled the cross-coupling of sp 3 C-H bonds and other substrates through the generation of sp 3 -hybridized carbon centered radicals (Scheme 4a).…”
Section: Magnus Ruepingmentioning
confidence: 99%
“…Over the past decade, metallaphotoredox catalysis has gained significant popularity in synthetic methodology. [21][22][23][24][25][26][27] This approach combines photocatalysis and transition metal catalysis to achieve the modular formation of C-carbon and C-hetero bonds. Specifically, the combination of photocatalytic HAT and transition metal catalysis has enabled the cross-coupling of sp 3 C-H bonds and other substrates through the generation of sp 3 -hybridized carbon centered radicals (Scheme 4a).…”
Section: Magnus Ruepingmentioning
confidence: 99%
“…[1][2][3][4][5][6] With the development of CÀ H functionalization strategy, transition metals have been proved to play an important role, which have been developed rapidly in organic chemistry. [7][8][9][10][11][12][13] Transition metal-catalyzed CÀ H functionalization strategy has been widely verified as one of feasible method in synthetic chemistry, which applied in material sciences, [14][15][16] pharmaceutical [17][18][19] and natural product synthesis. [2,20,21] Under this background, different kinds of CÀ H functionalization reactions was realized by employing different precious metals as catalysts, which due to the high catalytic activity, such as Pd, [22][23][24][25] Ir, [25][26][27] Rh, [28][29][30] Ru [31][32][33][34] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…C−H functionalization strategy has been considered as promising techniques applied in constructing complex molecular scaffolds not only in simple hydrocarbons, which ascribed to its atomic economy and low loss [1–6] . With the development of C−H functionalization strategy, transition metals have been proved to play an important role, which have been developed rapidly in organic chemistry [7–13] . Transition metal‐catalyzed C−H functionalization strategy has been widely verified as one of feasible method in synthetic chemistry, which applied in material sciences, [14–16] pharmaceutical [17–19] and natural product synthesis [2,20,21] .…”
Section: Introductionmentioning
confidence: 99%
“…The controlled formation of radical intermediates discloses a range of transformations that cannot be realized with traditional ionic chemistry. Moreover, since the seminal paper by MacMillan on the enantioselective α-alkylation of aldehydes, it has been shown that the photocatalytic cycle can be effectively combined with other types of catalysis such as organo- or transition metal catalysis. , Photoredox catalysts are fluorescent or phosphorescent compounds absorbing light and displaying, among other properties (e.g., suitable redox potential values), an excited state lifetime (τ) sufficiently long to allow quenching by other molecules in solution. Given the crucial importance of τ, this research area has been dominated by phosphorescent Ru- and Ir-complexes, whose photoredox properties may be tuned with careful choice of ligand(s).…”
Section: Introductionmentioning
confidence: 99%